Terjemahan nailul authar : himpunan hadits-hadits hukum - Faishal 'Abdul 'Aziz Alimubarak (Bina Ilmu, 1980)
tr, jil.3=c.1; jil.4=c.1/tr, jil.1=c.1-2/oen, jil.4=c.2; sn,jl.6,c.1; jl.1,c.3/tr, jil.2=c.1; jil.3=c.2; jil.4=c.3-4; jil.5=c.1-2/en, jil.3=c.3/stc13,jil.6,c.1